Visual perception problems in children with AD/HD, autism, and other learning disabilities : a guide for parents and professionals - Kurtz, Lisa A. (JKP essentials., 2006)
This book provides a comprehensive overview of vision problems in children with developmental disabilities such as AD/HD, autism spectrum disorders, and specific learning disabilities. Written in a very accessible style, it is appropriate for parents and professionals alike and offers non-technical explanations of how vision difficulties are screened for and advice on where to seek appropriate professional care. Lisa Kurtz outlines a range of activities for strengthening children's functional vision and perceptual skills using simple, homemade materials that are readily available in the home o.